TINJAUAN LENTUR DINDING BATA MERAH DENGAN PERKUATAN STRAPPING BAND ARAH RETAK HORIZONTAL (Studi kasus: dinding plesteran 1 cm dengan beban siklik quasistatik) - , JOHAN ARDIANTO ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Geologically, Indonesia is located in a very unstable area known as âthe ring of fireâ, a zone that tectonic earthquakes happens frequently. When earthquake happens, masonry wall will be vital to human safety. Reinforcement will be needed to provide a better seismic resistance of structure. Reinforcement can be done in two ways, by strenghtening, and increasing ductility. Increasing ductility will be the focus of this final project, by adding a polypropelene strapping band mesh to masonry wall. The aim of this research is to understand the behaviour of pp-band reinforced masonry wall under seismic load, especially on the increasement of damping ratio, and masonry wall ductility. In this research, 4 specimen were developed. One specimen treated as an unreinforced masonry wall, and the other 3 are reinforced with pp band mesh which have 10cm, 15cm, and 20cm of pitches variation. Each specimen have a same dimension of 120cm x 72cm x 10,3cm. Cyclic quasistatic load was used to simulate the seismic load. There are 12 cycle with a maximum deflection of 64mm. The cyclic test shows that pp band didnât work as a composite structure with masonry wall, because of pp band have less MOE than masonry wall. Before the first crack, seismic load were accumulated on the masonry wall, but after the first crack, strapping band started to have significant contribution. There are an increase in damping ratio, and ductility as the pitches narrowed. A reinforced wall with 15cm strap distance have the highest moment capacity of 1,44kNm/m, therefore masonry wall with 20cm and 10cm pitches have 1,137 kNm/m and 0,769 kN/m of moment capacity. After the masonry wall crack, pp band can provide a large load and deformation until the ultimate load.